(untitled) (International Journal of Technology and Management Research, 2020)
In recent years, the construction sector has undergone impressive developments in the use of ICT. Thus, placing much demands on capacity building that will produce an adequate, highly skilled workforce to manage the growing technology in the industry. ICT takes the front role and essentially becomes the medium in which all the other operations are carried out. Most researchers, thinkers and educators have taken up the challenge of using ICT since the 1980s with varied successes. For this reason, this paper assesses the extent to which ICT is used in the training of construction students in technical universities in Ghana. Quantitative method (questionnaire) was employed to elicit data from construction lecturers and students in five technical universities in Ghana. Descriptive statistics and factor analysis were adopted in analyzing the data. The research discovered that ICT adoption in training construction students in Ghanaian technical universities is very low. The study also established twenty-four (24) factors as constraints to ICT usage in construction students’ training in technical universities in Ghana. These come under "technology constraints", "economic constraints", "human constraints", "environmental constraints," and "administrative constraints". There is, therefore, a pressing need for a drastic shift towards integrating Construction related ICT tools in training construction students in Ghanaian technical universities. Citation: Ametepey, S. O., Gyadu-Asiedu, W. and Ansah, S. K. State of Information and Communication Technology (ICT) Usage in the Training of Construction Students in Ghanaian Technical Universities, 2020; 5(3): 86-95. Received: May 20, 2020 Accepted: September 30, 2020